Immune Responses to Epidermal Growth Factor Receptor (EGFR) and Their Application for Cancer Treatment - Sasada, Tetsuro; Azuma, Koichi; Ohtake, Junya; Fujimoto, Yuki (Frontiers in Pharmacology, 2016)
Epidermal growth factor receptor (EGFR) is a prototypic cell-surface receptor belonging to the ErbB/HER onocogene family. Overexpression or somatic mutations of EGFR have been reported to play an important role in tumorigenesis in various types of epithelial cancers. Therefore, targeting of EGFR with specific blocking antibodies or inhibitors have been developing for treatment for EGFR-associated tumors. Immune responses to HER2, another molecule of the ErbB/HER onocogene family, have been well studied, but only limited information on the immune responses to EGFR in cancer has been currently available. In this review, we have summarized the available data and discussed potential clinical importance of the anti-EGFR immune responses and EGFR-mediated immune regulation in cancer. Several lines of evidence suggest that cellular and humoral immune responses to EGFR might be useful as a marker and/or target for cancer therapy against EGFR-associated tumors. In addition, recent studies suggest the critical roles of EGFR-mediated signaling in regulation of expression of an immune checkpoint molecule, programmed death-ligand 1 (PD-L1) in tumor cells. Further studies are warranted to clarify the impact of the anti-EGFR immune responses and EGFR-mediated immunomodulation for clinical application for cancer treatment.